The Canterbury sound in popular music : scene, identity and myth - Draganova, Asya; Blackman, Shane; Bennett, Andy (Emerald studies in popular music and place, 2021)
This collection is a unique exploration of the heritage and legacy of the Canterbury Sound: a signature style emerging in the 1960s that draws upon psychedelic music, progressive rock, jazz and pop to capture the real and imagined interactions between people, place and music. The volume recounts the stories, and explores the significance, of the Canterbury Sound as heritage, ongoing legacy and scene. Originating from the experiences and ethnographic research of the three editors, all of whom have lived and worked in Canterbury, the book brings together reflections, stories, and critical insights from well-known musicians, researchers, DIY archivists and fans to explore the Canterbury Sound as an inter-generational phenomenon and a source of cultural identity. Associated with acts like Caravan, early Soft Machine, Robert Wyatt, and Kevin Ayers, this romanticised scene has a special place in popular music culture. Chapters examine the emergence of the Canterbury Sound and the associated scene, including the legacies of key figures in forming the Canterbury Sound aesthetic, the documentation of the scene (online and off) and contemporary scenes within the city, which continues to attract and inspire young people.